PENINGKATAN HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN DATAR MELALUI MODEL DISCOVERY LEARNING BERBANTUAN MEDIA KONKRET PADA SISWA KELAS IV SD - Ni Kadek Lolita Amaria; I Made Sujana Adnyana (STKIP Subang, 2026)
This study was motivated by the low mathematics learning outcomes of fourth-grade elementary school students on the topic of plane figures. The problem was influenced by teacher-centered learning practices, monotonous instructional methods, and the limited use of concrete learning media. This study aimed to improve students’ mathematics learning outcomes through the implementation of the Discovery Learning model assisted by concrete media. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The study was carried out at SD N 1 Datah involving 16 fourth-grade students. Data were collected through learning outcome tests and observation sheets, then analyzed using descriptive quantitative and qualitative techniques. The findings indicated that the application of the Discovery Learning model supported by concrete media was able to enhance students’ mathematics learning outcomes, as reflected in the increase in the average scores and the percentage of learning mastery from the first cycle to the second cycle. Therefore, the use of the Discovery Learning model assisted by concrete media is considered effective in improving mathematics learning outcomes on the topic of plane figures for fourth-grade students.